(untitled) (Journal of the Bangladesh Agricultural University, 2016)
The experiments were carried out during 2009 to 2013 on diagnosis and prescriptions for management of Cercospora leaf spot of chilli. The studies were undertaken in 250 growers field of five upazillas viz. Mymensingh sadar, Kushtia sadar, Kumarkhali, Chandina and Sher-e-Bangla Nagar. The highest disease incidence (38.6%) and severity (17.4%) of Cercospora leaf spot of chilli was recorded. Cercospora capsici produced leaf spot of chilli. The prescription given by Plant Disease Diagnostic Clinic (PDDC) was effective in the farmers field against the disease. Cercospora leaf spot of chilli is the most important diseases of spices in Bangladesh as the diseases significantly reduce the quality and yield. Prescription was Bavistin-50 DF @ 1g/l sprayed 4 times at 15 days interval for management of Cercospora leaf spot of chilli. The practices reduced the incidence by 72.82%, severity by 65.60%. The yield increased by 35.11%. Benefit cost ratio (BCR) was 3.34. J. Bangladesh Agril. Univ. 13(2): 191-196, December 2015